The Degree of Awareness of the Students at the University of Jordan towards the Concept of Digital Citizen - Abbasi, Dina Karam Tawfiq; Hamdi, Narjes Abdelqader Ismaeel (Dirasat: Educational Sciences, 2020)
The study aims at investigating the degree of awareness of the students at the University of Jordan towards the concept of Digital Citizen, and its relationship to Gender, faculty, and the academic level by using the analytical descriptive approach. The study population consisted of all students at the University of Jordan enrolled in the academic year 2017/2018. The study sample consisted of (500) students who were stratified randomly selected. In order to achieve the aim of the study, a questionnaire consisted of (36) items was applied. The results showed that the degree of awareness of the students at the University of Jordan of the concept of the Digital Citizen was moderate and there were no significant statistical differences in the awareness degree among students due to their gender, faculty and the academic level. In light of the study results, the researchers recommend raising the University of Jordan students’ awareness of digital citizenship and digital citizen through the educational stages in Jordan and urging those in charge of the instructional curricula to include the concept of digital citizen in these curricula.